PROFIL KONDISI FISIK TIM BOLA VOLI PEMULA PUTRA MTS ROUDLOTUL ULUM BONO TAPUNG - Azkiya, Lu'luatul; Sulastio, Agus; ,, Rusmanto (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2025)
Abstract: The problem in this research is that the athlete has a physical condition that is less than optimal or still needs improvement in several aspects of physical condition because in approximately five matches and during sparring he always loses the game, and the researcher sees that there are deficiencies or weaknesses in the athlete, namely; when the ball serve does not go over the net or does not enter the opponent's area, secondly when smashing is not good due to the blow being not strong enough and the ball often gets caught in the net, thirdly the athlete's passing is often uncontrolled, fourthly the block, when making the block the jump does not reach and finally the athlete is less nimble or less agile when receiving the ball is difficult. Therefore, athletes need physical conditioning training to train muscle strength, speed, agility, flexibility and explosive power. The aim of this researcher is to determine the Physical Condition Profile of the Men's Volleyball Beginner Team at MTs Roudlotul Ulum Bono Tapung. This research method is quantitative research with a descriptive approach, namely collecting data to obtain information related to phenomena. The population in this research was 13 students at MTs Roudlotul Ulum Bono Tapung. The instruments used in this research are observation, tests and measurements. The data analysis technique uses the t test, to determine the results of the physical condition profile after treatment or training is given. Based on the results of research on the physical condition of MTs Roudlotul Ulum beginner volleyball athletes, it can be concluded that the